2011
DOI: 10.1093/brain/awr161
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of gliosis to diffusion tensor anisotropy and tractography following traumatic brain injury: validation in the rat using Fourier analysis of stained tissue sections

Abstract: Diffusion tensor imaging is highly sensitive to the microstructural integrity of the brain and has uncovered significant abnormalities following traumatic brain injury not appreciated through other methods. It is hoped that this increased sensitivity will aid in the detection and prognostication in patients with traumatic injury. However, the pathological substrates of such changes are poorly understood. Specifically, decreases in fractional anisotropy derived from diffusion tensor imaging are consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
377
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(419 citation statements)
references
References 66 publications
37
377
3
Order By: Relevance
“…In recent animal experiments of traumatic brain injury a similar DTI pattern has been associated with gliosis at the histopathologic level. 24 Unlike FA, AD did not provide added predictive value with regard to WMH accrual, compared with a regression model that included only baseline WMH volume (Table 4). Future studies using more sophisticated DTI techniques employing multiple or higher b-values compared with the standard DTI, such as high angular resolution diffusion imaging 25 or composite hindered and restricted model of diffusion, 26 as well as DTI-pathology combination studies may provide meaningful information to better understand the histopathologic substrate of DTI changes in the GM.…”
Section: Discussionmentioning
confidence: 95%
“…In recent animal experiments of traumatic brain injury a similar DTI pattern has been associated with gliosis at the histopathologic level. 24 Unlike FA, AD did not provide added predictive value with regard to WMH accrual, compared with a regression model that included only baseline WMH volume (Table 4). Future studies using more sophisticated DTI techniques employing multiple or higher b-values compared with the standard DTI, such as high angular resolution diffusion imaging 25 or composite hindered and restricted model of diffusion, 26 as well as DTI-pathology combination studies may provide meaningful information to better understand the histopathologic substrate of DTI changes in the GM.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a recent controlled cortical impact (CCI) study on rats 80 showed significantly increased RD and decreased FA in WM. RD may also be selectively sensitive to alterations of the myelin sheath, 81 as shown in the mouse model 22,82 and, more recently, in optic neuritis.…”
Section: Longitudinal Dti Study Of Wm Tracts After Srcmentioning
confidence: 99%
“…Additionally, recent animal models indicate increased anisotropy within the thalamus and hippocampus during acute and more chronic injury phases. 6,7 Although evidence of atrophy has been found as early as 1 to 3 weeks postinjury in moderate to severe TBI,8,9 it becomes more prevalent at 6 to 12 months, 10-13 even in the absence of macroscopically detectable lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent animal models indicate increased anisotropy within the thalamus and hippocampus during acute and more chronic injury phases. 6,7 Although evidence of atrophy has been found as early as 1 to 3 weeks postinjury in moderate to severe TBI, 8,9 it becomes more prevalent at 6 to 12 months, [10][11][12][13] even in the absence of macroscopically detectable lesions. 14,15 Studies of patients with complicated 16 and symptomatic mild to moderate 17 TBI indicate atrophy as a function of disease progression approximately 6 months 16 or 1 year 17 postinjury.…”
mentioning
confidence: 99%